Effect of Sustained Elevated Gastric pH Levels on Gefitinib Exposure. Issue 5 (8th February 2017) - Tang, Weifeng; Tomkinson, Helen; Masson, Eric
Abstract: This open‐label, randomized, phase 1 crossover study investigated the effect of elevated gastric pH level (>5) on the relative bioavailability and pharmacokinetic profile of the epidermal growth factor receptor tyrosine kinase inhibitor gefitinib. Healthy male volunteers (n = 26) were randomized to gefitinib 250 mg (fasted), either alone on day 1 (unmodified gastric pH) or 1 hour following the second of 2 oral doses of the H2 ‐receptor antagonist ranitidine 450 mg (elevated gastric pH). After a 3‐week washout period, volunteers crossed to the other treatment. The geometric least‐squares (GLS) mean AUC0–∞ and Cmax for gefitinib were reduced by 47% and 71%, respectively, under conditions of sustained elevated gastric pH; for both parameters, the 90%CI for the ratio of the GLS means lay below the prespecified lower limit. Median tmax was delayed from 5 to 6 hours. Mean t1/2 was similar under both gastric pH conditions. No serious adverse events were reported. The bioavailability of a single oral gefitinib 250‐mg dose was reduced by approximately 50% when gefitinib was administered under conditions of sustained elevated gastric pH.